IncobotulinumtoxinA for the Treatment of Glabellar Frown Lines: A Prospective, Multicenter, Single-arm Study in Taiwan - Chao, Yates Yen-Yu (J Clin Aesthet Dermatol, 2019)
Objective: We assessed clinical effectiveness, longevity of treatment effects, and patient satisfaction with incobotulinumtoxinA for glabellar frown lines (GFL) treatment in Asian patients. Design, Setting, and Participants: This was a prospective, multicenter, single-arm, open-label study at six sites in Taiwan. Patients aged 20 to 65 years with mild to very severe GFLs (Merz scale: 1–4 points) were eligible; 45 patients [including 23 BoNT/A-naïve and 22 previously-treated (“switch”) patients were enrolled. Patients received intramuscular incobotulinumtoxinA injection at up to five injection points. Total doses ranged from 12 to 20U. Measurements: Investigators assessed improvements in dynamic GFLs at Days 14 and 120 using the validated five-point Merz scale (0=no lines; 4=very severe lines). Treatment satisfaction was self-reported by patients via questionnaire. Results: All patients showed excellent response to treatment in that Merz scores at Day 14 were 0 or 1 point(s). Both groups showed a mean improvement of 2.9 points; the response rate (1-point improvement or more from baseline) was 100 percent. GFL improvement was maintained over at least four months in both groups (mean improvements at Day 120: 1.5 points, naïve; 1.7 points, switch). Patient satisfaction ratings remained high (almost 100% in both groups) throughout the study. There were no statistically significant differences between groups regarding treatment satisfaction or GFL improvement (Merz score) at Days 14 and 120. No adverse events occurred. Conclusion: In Asian patients, incobotulinumtoxinA treatment for dynamic GFLs is effective and long lasting, with no expected differences between BoNT/A-naïve patients and those switching from other BoNT/As. IncobotulinumtoxinA yields consistent and natural-looking results for first and subsequent treatments.